2020
DOI: 10.3390/ma13092117
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Behavior of Chloride Ions in Concrete Box Girder under the Influence of Load and Carbonation

Abstract: In order to study the durability degradation characteristics of concrete box girder under load and carbonation and chloride ion erosion, a scale model of concrete box girder was made for experimental research. According to the test results, the diffusion characteristics of chloride ions in the concrete box girder under the coupling effect of load and carbon dioxide were analyzed. By revising the calculation formula of the existing chloride ion concentration considering multiple factors, a calculation model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Among them, the 28-day measured compressive strength of concrete used for indoor accelerated carbonation is 49.6 MPa. The specific size, mix proportion, and material composition of the concrete box girder model can be found in the literature [42].…”
Section: Formula Verificationmentioning
confidence: 99%
“…Among them, the 28-day measured compressive strength of concrete used for indoor accelerated carbonation is 49.6 MPa. The specific size, mix proportion, and material composition of the concrete box girder model can be found in the literature [42].…”
Section: Formula Verificationmentioning
confidence: 99%
“…The steel, which is initially shielded by the concrete coating, can lose its protective properties due to either carbonation caused by carbon dioxide or the infiltration of chloride ions from seawater, sea spray, or de-icing salts [4]. This phenomenon poses a greater risk when the structure is exposed to mechanical strain [5] and deteriorates progressively [6], [7]. The interplay between stress levels and age contributes to a fluctuation in the diffusion coefficient, thereby expediting the progression of mechanical or physicochemical pathology that can impact concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in Refs. [28][29][30][31] analyzed the influence of chloride ions and described the electroosmotic effect as a process of movement intensification in capillary-porous objects. The analyses showed that this process can descriptively characterize the electrochemical reaction of oxygen reduction in concrete, as well as the electrolysis of water.…”
Section: Introductionmentioning
confidence: 99%